Longitudinal changes in adolescents with TOF: implications for care. (22nd December 2016) - Bhat, Misha; Mercer-Rosa, Laura; Fogel, Mark A.; Harris, Matthew A.; Paridon, Stephen M.; McBride, Michael G.; Shults, Justine; Zhang, Xuemei; Goldmuntz, Elizabeth
Abstract : Background: We sought to identify predictors of change in right ventricular function and exercise capacity in adolescents following repair for tetralogy of Fallot. Methods and results: We performed a longitudinal study with serial cardiac magnetic resonance imaging and/or exercise stress tests. Patients with interim intervention on the pulmonary valve were excluded. Paired t -test was used to detect longitudinal changes and multivariable regression models were built to identify predictors of change. Initial and follow up magnetic resonance and exercise stress test studies were available for 65 and 63 subjects, respectively. Age at initial testing was 11.7 ± 2.7 years. Average follow up time was 4.5 ± 1.8 (magnetic resonance) and 4.0 ± 1.6 (exercise test) years. There was a significant increase in right ventricular end diastolic and systolic volume (119 ± 34 to 128 ± 35 ml/m 2, P = 0.006; 49 ± 20 to 56 ± 23 ml/m 2, P = 0.001, respectively), and a decrease in right ventricular ejection fraction (60 ± 7 to 56 ± 8%, P = 0.001), with no significant change in pulmonary regurgitant fraction or right ventricular cardiac index. Predictors of right ventricular dilation over time included: time elapsed from surgical repair, severity of pulmonary insufficiency and right ventricular dilation at the initial magnetic resonance imaging. Of those, time elapsed from surgical repair had the most significant effect. There was no change in exercise capacity. Discussion: In the adolescent with tetralogy of Fallot, longer time from surgery, more pulmonary insufficiency and greater right ventricular dilation at initial magnetic resonance imaging are associated with progressive right ventricular dilation. These results suggest early monitoring with magnetic resonance imaging might identify those at highest risk for progressive disease.